2017
DOI: 10.3389/fmolb.2017.00075
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Replication and Repair for the Development of Novel Therapeutics against Tuberculosis

Abstract: Mycobacterium tuberculosis is the etiological agent of tuberculosis (TB), an infectious disease which results in approximately 10 million incident cases and 1.4 million deaths globally each year, making it the leading cause of mortality from infection. An effective frontline combination chemotherapy exists for TB; however, this regimen requires the administration of four drugs in a 2 month long intensive phase followed by a continuation phase of a further 4 months with two of the original drugs, and is only ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 207 publications
(200 reference statements)
0
50
0
Order By: Relevance
“…These second generation fluoroquinolones are safe, well tolerated, and have longer serum half‐life in the range of 4–10 h. In addition to these, newly synthesized 8‐methoxy fluoroquinolones, DC‐159a, is highly potent against drug susceptible, quinolone resistant bacteria and is currently in preclinical development stage . Furthermore, small molecules such as novobiocin, thiazolopyridine, benzofurans, thiazolopyridone ureas, and SPR‐720 have also been identified as inhibitors of GyrB subunit of DNA gyrase . In addition to DNA gyrase, other enzymes involved in DNA replication are also being explored as targets for anti‐tubercular agents .…”
Section: Screening Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…These second generation fluoroquinolones are safe, well tolerated, and have longer serum half‐life in the range of 4–10 h. In addition to these, newly synthesized 8‐methoxy fluoroquinolones, DC‐159a, is highly potent against drug susceptible, quinolone resistant bacteria and is currently in preclinical development stage . Furthermore, small molecules such as novobiocin, thiazolopyridine, benzofurans, thiazolopyridone ureas, and SPR‐720 have also been identified as inhibitors of GyrB subunit of DNA gyrase . In addition to DNA gyrase, other enzymes involved in DNA replication are also being explored as targets for anti‐tubercular agents .…”
Section: Screening Approachesmentioning
confidence: 99%
“…Furthermore, small molecules such as novobiocin, thiazolopyridine, benzofurans, thiazolopyridone ureas, and SPR‐720 have also been identified as inhibitors of GyrB subunit of DNA gyrase . In addition to DNA gyrase, other enzymes involved in DNA replication are also being explored as targets for anti‐tubercular agents . For example, Kling et al, recently showed that DnaN, encoding β‐sliding clamp of M. tuberculosis , is the target for both methyl and cyclo‐hexyl derivatives of Griselimycin (SATB‐082) .…”
Section: Screening Approachesmentioning
confidence: 99%
“…Hydroxyproline has been also proposed as a biomarker for tuberculosis (TB; Mach et al, 1973;Garcia-Zamalloa & Taboada-Gomez, 2012), the disease caused by Mycobacterium tuberculosis , since hydroxyproline is produced in TBassociated pulmonary fibrosis (Hernandez-Pando et al, 2004). Moreover, proline metabolism has been suggested as a promising target for the development of anti-infectives (Forlani et al, 2012), and the inhibition of this pathway could be taken into account for the development of potent anti-TB medicines, adding to the repertoire of (NADH-dependent) enzymes under consideration for the development of potent anti-TB medicines and adding to the repertoire of enzymes that have been considered as valid targets for the development of new antitubercular drugs, such as enzymes belonging to nucleotide-biosynthetic pathways (Paolino et al, 2018;Ferraris research papers et al, 2014Ferraris research papers et al, , 2015Sahu et al, 2018;Chacko et al, 2018;, to DNA-repair multi-step cascades and direct damage reversal pathways (Miggiano et al, 2016Morrone et al, 2017;Lahiri et al, 2018), and to DNA replication pathways (Reiche et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to the most recent WHO report [8] the threat that TB presents to world health has been considerably heightened by the evolution and unfolding of drug-resistant TB: in 2015, a staggering 480,000 persons across the globe developed multi-drug resistant (MDR)-TB, outlined as TB that's proof against Rifampicin (RIF) and INH (INH), with or while not resistance to different first-line anti-tubercular medicine. Sadly, this example must continue to worsen victimization the XDR-TB to kinds of the un wellness that are functionally untreatable with existing antibiotics [15]. Camel urine has been consumed extensively for years in Saudi Arabia because it believed to be able to treat a large variety of diseases like cold, fever, or even cancer.…”
Section: Discussionmentioning
confidence: 99%